The Impact of Electronic Banking on the Financial Performance of Financial Institutions in Uganda: A Case Study Pride Microfinance Limited - Molly Komuhangi (Uganda Christian University, 2024)
The aim of the study was to establish how ebanking influences the operational efficiency of financial institutions in Uganda, using Pride Microfinance Limited as a case study. The study was conducted to find out the following: to establish different types of e-banking used by Pride Microfinance Limited; determine whether there is any relationship between e-banking and the performance of Pride Microfinance Limited; and establish how much e-banking contributes to the general performance at Pride Microfinance Limited. Descriptive research was adopted for data collection and analysis; the data included both qualitative and quantitative data. A total of 85 purposive and random samples have been selected from the target population of 115. Data collection was carried out using structured and unstructured questionnaires. Descriptive data such as percentages have been used to illustrate the many manifestations of electronic banking. Further, inferential statistics were used to measure the correlation and influence that electronic banking has had on the performance of financial organizations. This implies that 97.3% of the operational efficiency is brought about by ebanking. There is a significant positive effect of e-banking on the operational efficiency of Pride Microfinance Limited. Pride Microfinance Limited may conduct workshops and training on e-banking technology for its customers to enable its customers to improve their understanding and use of the technology.